Ceratopteris baguangensis (Pteridaceae), a new species of Ceratopteris from Guangdong, China - Li, Zixiang; Xia, Zengqiang; Lin, Lin; He, Chunmei; Luo, Lin; Xing, Fuwu; Wang, Faguo (Phytotaxa, 2024)
A new species of fern, Ceratopteris baguangensis was recently discovered in Shenzhen, Guangdong, China. Detailed morphological descriptions and photographs of the habitat are shown. C. baguangensis is similar to C. thalictroides and C. oblongiloba in the morphology of the fertile fronds but is distinct from them in the lobes of the sterile fronds. Furthermore, the chloroplast genome of C. baguangensis was sequenced and characterized. The annotated results revealed that the chloroplast genome had a conserved quadripartite structure, with a pair of inverted repeat regions (IRs) separating the large single copy (LSC) region and the small single copy (SSC) region, resulting in a total length of 149,755 base pairs (bp). The genome encodes a total of 120 unique genes, including 76 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. Molecular evidence indicated that the C. baguangensis formed a distinct lineage and was sister to C. oblongiloba. Given the current population size of C. baguangensis in Baguang Heritiera littoralia Wetland Park, it is suggested C. baguangensis should be categorized as an Endangered (EN) species according to the criteria of IUCN. This study further enriches the diversity of the genus Ceratopteris and will help to elucidate their phylogenetic relationships.